AB1169 Can ultrasound-detected synovitis predict radionuclide synovectomy efficacy in chronic inflammatory rheumatism?. (12th June 2018) - Amouzougan, A.S.; Marotte, H.; Boussoualim, K.; Mijola, L.; Collet, P.; Pallot-Prades, B.; Prévot-Bitot, N.; Barral, F.-G.; Thomas, T.
Abstract : Background: The better management of inflammatory joint diseases, including biological treatments, has not eliminated in the clinical practice the persistence of chronic inflammatory monoarthritis despite local glucocorticosteroids (GC) injection and optimal systemic treatment. No therapeutic consensus was proposed in this clinical situation. In addition, radionuclide synovectomy (RS) was proposed with no clear benefit-risk effect. However, it has been shown that ultrasound-detected residual synovitis is frequent and predictable to relapse and structural progression in rheumatoid arthritis patients. Objectives: We explored ultrasound-detected synovitis predictive value of response to RS in chronic inflammatory monoarthritis. Methods: A monocentric prospective study was performed including unclassified monoartrhitis, rheumatoid arthritis, spondyloarthritis, and lupus between January 2012 and December 2017. All patients already received GC intra-articular injections (GCI) and were treated in particular by cs or bDMARDS. On the day of the RS performed by a radiologist under radioscopic control, all patients had an articular power Doppler (PD;0–3) with greyscale (GS;0–3) ultrasonography with a MyLab 60 – EASAOTE, by 2 experimented sonographers. Primary endpoint (EP) was subjective overall improvement ≥50% without of any GCI and/or surgical management at 6 months (M). Chi-square test was used to check the difference between groups. Results: Data from 23 patients, 17 women and 6 men, with mean age 54±14 years were analysed. Eleven RA ( 45.5% RF +or ACPA+ ), 3 pSpA, 2 axSpA HLA B27+, 1 Lupus, and 6 unclassified monoartrhitis ( FR and ACPA- ). Histological analysis of the synovium in 7 patients concluded to chronic nonspecific synovitis. Twenty eight joints were treated. Of them, 25 were coted US GS ≥2 and/or DP ≥2. None had US GS=0 and DP=0. Effusion on US exam was reported in 24 joints. On X-ray, 46.4% of patients had joint space narrowing and/or erosion. ESR or CRP increased in 43.5%. Forty five previous GCI were declared ( Cortivazol or triamcinolone hexacetonide ), with a median at 2. 1–6 Patients were treated with methotrexate, n=16 (69.6%), hydroxychloroquine, n=1, bDMARDS, n=11 (48%), oral GC, n=8 (35%) and non-steroidal anti-inflammatory drug, n=6 (26%). At M6 and M12, 64.6% of patients reached the EP. One patient reached the EP only at M12 and another one only at M6. No significant differences were observed between groups in terms of PDUS (DP ≥2 vs DP ≤1), unclassified monoartrhitis, and joint space narrowing and/or erosion. Only one patient had pain exacerbation 24 hour after RS followed by a quick recovery. Conclusions: In chronic inflammatory monoarthritis, PDUS was not predictive of clinical outcome after RS. However, this intra-articular procedure appeared effective in either unclassified or classified monoarthritis or in presence of radiographic joint lesions. Disclosure of Interest: None declared